Estudo da influência dos metais e do método de síntese de materiais com estrutura perovsquita nas propriedades adsortivas em meio líquido - Lemos, Jéssica Aline Santos (2022)
Mixed oxides with perovskite structure are typically crystalline materials that have many applications due to their magnetic, electrical, catalytic and optical properties. In addition, they have recently excelled in environmental applications for contaminant removal due to their adsorptive and regeneration characteristics. The efficiency of the application of these materials is related, among other factors, to their composition and route of synthesis. The results of the work are organized into topics, with topic I reporting and discussing the synthesis of materials of the LaMO3 type (M= Mn, Fe, Co and Ni) by the grinding method and evaluation of its use as an adsorbent. The results showed the confirmation of all materials synthesized through X-Ray Diffraction and the removal efficiencies ranged from 51 to 97% for the removal of Turquoise Blue dye in aqueous solution, where the material with nickel in the B site (LN-M9 ) achieved an adsorption of 97%. In topic II, the effect of partial doping with calcium in materials of the LaMO3 type (M= Mn, Fe, Co and Ni) obtained by the milling method on the removal efficiency of the turquoise blue dye was evaluated. The results showed removal efficiencies between 49 and 89%, values lower than the materials without doping. The influence of the synthesis method on the adsorptive properties of materials such as LaNiO3 and La0.5Ca0.5NiO3 was discussed in topic III. The results revealed that the materials synthesized by the milling method showed greater removal efficiencies for the Blue Turquoise dye in aqueous solution when compared to the modified protein method, using collagen as a chelating agent. The recovery and reuse of adsorbents were addressed and discussed in topic IV, where the LaNiO3 perovskite synthesized by the modified protein method resisted the dye adsorption conditions in aqueous media, in addition to withstanding the high calcination temperature used in the adsorbent recovery. The application of adsorption in cycles revealed the possibility of the material being applied for 6 consecutive times without losing its effectiveness in removing the turquoise blue dye, maintaining removal values of approximately 93%. The present work brings studies and discussions about the influence of the metals that compose the A site and the method of synthesis of materials with the perovskite structure applied in the removal of dyes from the aqueous medium. Therefore, this type of work is of great importance for science as well as for industry, as it allows the development of new materials in the light of scientific knowledge for the benefit of society.